Design and fabrication of magnetorheological elastomer vibration isolator / Ubaidillah ... [et al.] - Ubaidillah, Ubaidillah; Hadi, Syamsul; Harjana, Harjana; Hairuddin, Khairunnisa; Mazlan, Saiful Amri (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Universal vibration isolator uses thin layer magnetorheological elastomers (MREs). This article presents a development of cone-shaped MREs based vibration isolator featuring thick MREs. This work begins with a prototype design, magnetic circuit evaluation, prototype fabrication, and cyclic load preliminary tests. In this article, finite element magnetic method (FEMM) was used to design the electromagnetic circuit. An innovative magnetic circuit design is proposed for MREs isolator with cone shape MREs materials. MREs and shaft are adopted as magnetic core together with steel housing. MREs are placed at the end of each shaft and attached to the housing to form an enclosed magnetic path in the isolator. FEMM results showed that this novel design can provide sufficient magnetic field to all MREs region. Finally, the influence of input current to the MREs isolator on magnetic field strength is investigated. It is found that the magnetic field in MREs isolator increase with the increase of the input current.